Continuous Oral Administration of the Superantigen Staphylococcal Enterotoxin C2 Activates Intestinal Immunity and Modulates the Gut Microbiota in Mice - Gu, Wu; Zhang, Huiwen; Zhang, Zhichun; Xu, Mingkai; Li, Xiang; Han, Zhiyang; Fu, Xuanhe; Li, Xu; Wang, Xiujuan; Zhang, Chenggang (Advanced science, 2024)
Staphylococcal Enterotoxin C2 (SEC2), a classical superantigen, is an antitumor immunotherapy agent. However, the injectable formulation of SEC2 limits its clinical application. Here, it is reported that oral administration of SEC2 activates the intestinal immune system and benefits intestinal health in a mouse model. These results indicate that intact SEC2 is detected in the stomach, intestine, and serum after oral administration. Continuous oral administration of SEC2 activates immune cells in gut‐associated lymphoid tissues, promoting extensive differentiation and proliferation of CD4+ and CD8+ T cells and CD19+ B cells, leading to increased production of cytokines and secretory immunoglobulin A. SEC2 also enhances intestinal barrier function, as demonstrated by an increased villus length/crypt depth ratio and elevated expression of mucins and tight junction proteins. Additionally, SEC2 indirectly influenced gut microbiota, reinforcing potential probiotics and short‐chain fatty acid synthesis. Enhanced differentiation of T and B cells in the spleen, coupled with elevated serum interleukin‐2 levels, suggests systemic immune enhancement following oral administration of SEC2. These findings provide a scientific basis for the development of SEC2 as an oral immunostimulant for immune enhancement and anti‐tumor immunotherapy. Orally administered staphylococcal enterotoxin C2 (SEC2) acts directly on the intestinal mucosal immune system, stimulating the differentiation of T and B cells in the intestine. SEC2 also indirectly alters the structure of the gut microbiota, enhances the production of metabolite short‐chain fatty acid, and improves intestinal barrier function. Thereby, orally administered SEC2 achieves systemic immune enhancement without significant immune‐related side effects.